2021
DOI: 10.5815/ijisa.2021.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Point Based Forecasting Model of Vehicle Queue with Extreme Learning Machine Method and Correlation Analysis

Abstract: Traffic is a medium to move from one point to another. Therefore, the role of traffic is very important to support vehicle mobility. If congestion occurs, mobility will be hampered so that it gives influence to other sectors such as financial, air pollution and traffic violations. This study aims to create a model to predict vehicle queue at the traffic lights when its status is red. The prediction is conducted by using Neural Network with Extreme Learning Machine method to predict the length of the vehicle qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Correlation analysis [25,26] was conducted with the help of SPSS 25.0, and the results showed that psychological contract breakdown was positively correlated with turnover intention (r=0.420**) and perceived opportunity (r=0.373**), negatively correlated with job satisfaction (r=-0.260**), and job embeddedness (r=-0.473**), which preliminarily verified that H1, H2a, H3a, and H4a. Note๏ผš** indicates significant correlation at the 0.01 level (two-tailed).…”
Section: Correlation Analysismentioning
confidence: 99%
“…Correlation analysis [25,26] was conducted with the help of SPSS 25.0, and the results showed that psychological contract breakdown was positively correlated with turnover intention (r=0.420**) and perceived opportunity (r=0.373**), negatively correlated with job satisfaction (r=-0.260**), and job embeddedness (r=-0.473**), which preliminarily verified that H1, H2a, H3a, and H4a. Note๏ผš** indicates significant correlation at the 0.01 level (two-tailed).…”
Section: Correlation Analysismentioning
confidence: 99%
“…๐ป โ€  = (๐ป ๐‘‡ ๐ป) โˆ’1 ๐ป ๐‘‡ (8) Secara lebih ringkas, algoritma ELM dengan SLFN dapat dimodelkan dengan langkah sebagai berikut [20], [12], [21], [22]. Input : Data training (๐‘ฅ ๐‘– , ๐‘ฆ ๐‘– ) dengan ๐‘ฅ ๐‘– = [๐‘ฅ ๐‘–1 , ๐‘ฅ ๐‘–2 , โ€ฆ , ๐‘ฅ ๐‘–๐‘‘ ] ๐‘‡ โˆˆ ๐‘… ๐‘‘ dan ๐‘ฆ ๐‘– = [๐‘ฆ ๐‘–1 , ๐‘ฆ ๐‘–2 , โ€ฆ , ๐‘ฆ ๐‘–๐‘š ] ๐‘‡ โˆˆ ๐‘… ๐‘š .…”
Section: ๐ป๐›ฝ = ๐‘Œunclassified
“…After the basic simulation of the type and number of faults and the extraction of the characteristic quantities for the building electrical systems and fault states, the appropriate algorithm must be used to model them, and then the model must be used for fault identification and diagnosis. BP neural networks are widely used in current fault diagnosis due to their multihidden layer structure, which increases the computational power of diagnosis [26]. However, BP neural networks also have some obvious drawbacks, resulting in slow convergence of the computational results, or not easy convergence.…”
Section: Building Electrical System Fault Diagnosis and Monitoring Co...mentioning
confidence: 99%